Planning and Developing Interpretive Facilities - Linking Visitors and Protected Area : a Case Study from Panna Tiger Reserve - Sinha, Bitapi C. (Indian Forester, 2007)
The paper deals with the challenge in interpreting the diverse resources, from Diamonds to Tigers, for the diverse audience from international visitors to the locals. More so to interpret in such a way that the locals care for the resources in the Reserve and the visitors enjoy the visit. Research, identifying resources, training nature guides, developing website, orientation film, publications, Interpretation Centre, Visitor Centre - how it was done in Panna Tiger Reserve.